The effect of brine mass rate on circumferential and longitudinal stress in vertical type separator design. Issue 1 (1st January 2019) - Wuryanti, Sri; Fitriyani, Yelly
Abstract: The geothermal power plant is converting steam to electricity. The evaporation process in the evaporator produces wet steam (brine). The Brine has a high temperature and contains water, which is quite dominating. Therefore, a separator is needed to separate between ammonia-rich vapor that will flow into the turbine and ammonia-poor liquid, which will flow to the regenerator. In this case, the optimal separation uses a vertical separator. The design of vertical separator produces the specifications for brine mass flow rates 55.275 kg/s at circumferential stress 614.93 bar and brine mass flow rates 1.124 kg/s at longitudinal stresses of 1229.87 bar. The analysis result of brine mass flow rate on the lowest circumferential stress was 16.583 kg/s at 573.71 bar, and the highest was 181.372 kg/s at 628.94 bar, while the brine mass flow rate on the lowest longitudinal stress was 1.048 kg/s at 1, 147.42 bar and the highest is 1.149 kg/s at 1, 257.88 bar.